2014
DOI: 10.1111/tpj.12524
|View full text |Cite
|
Sign up to set email alerts
|

Apple MdABCF assists in the transportation of SRNase into pollen tubes

Abstract: SUMMARYSelf-incompatibility (SI) is a reproductive isolation mechanism in flowering plants. Plants in the Solanaceae, Rosaceae and Plantaginaceae belong to the gametophytic self-incompatibility type. S-RNase, which is encoded by a female-specific gene located at the S locus, degrades RNA in the pollen tube and causes SI. Recent studies have provided evidence that S-RNase is transported non-selectively into the pollen tube, but have not specified how this transportation is accomplished. We show here that the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 50 publications
(71 reference statements)
2
75
0
Order By: Relevance
“…The transient expression vector pEZS-NL harboring an EGFP-tag [31] was used to study the transformation efficiency in response to PEG concentrations and transfection time (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transient expression vector pEZS-NL harboring an EGFP-tag [31] was used to study the transformation efficiency in response to PEG concentrations and transfection time (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…In order to select the optimal concentration of PEG4000, concentrations of 10, 15, 20, 25 and 30% PEG4000, w/v were tested. Next, 20 µg of the pEZS-NL plasmid, which contained a 35S promoter and the coding sequence fused to EGFP and OCS 3′ terminator which can used for transient expression [31] (Isolated by PureLink ® Quick Plasmid Miniprep Kit, Invitrogen, cat. no.…”
Section: Methodsmentioning
confidence: 99%
“…The endogenous cytosolic PPase activity decreased and the PPi levels increased in SPI‐treated pollen tubes compared with those that were CPI‐treated, suggesting that MdPPa is involved in the SI response. Interestingly, we found that non‐self S ‐RNase is largely absent from the cytosol of growing pollen tubes after 120 min of culture, implying that non‐self S ‐RNase is degraded by the 26S proteasome, as we have shown previously that both self and non‐self S ‐RNases are taken up by growing apple pollen tubes (Meng et al ., ,b). Moreover, there may be some low‐level interactions between MdPPa and non‐self S ‐RNases in CPI treatment, resulting in a weak reduction in pollen growth and MdPPa activity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent model has proposed that, when taken up nonspecifically through the action of an ABCF protein, S ‐RNase is recognized by collaborative non‐self SLF/SFBB proteins and degraded via the ubiquitin‐26S‐proteasome pathway in a non‐self‐pollen tube. By contrast, when recognition does not occur, the S ‐RNase has a cytotoxic effect inside the self‐pollen tube, resulting in an inhibition of pollen tube growth (Luu et al ., ; Qiao et al ., ; Hua & Kao, ; Kubo et al ., ; Minamikawa et al ., ; De Franceschi et al ., ; Meng et al ., ; Yuan et al ., ). Another compartmentalization model has also explained why S‐RNase has a specific cytotoxic effect on self‐pollen tubes, but not on non‐self‐pollen tubes.…”
Section: Introductionmentioning
confidence: 99%
“…S-RNase was observed to be non-selectively taken up by in vitro cultured apple pollen tubes. The uptake appeared to be mediated by the cytoskeleton and an ABC transporter family protein (MdABCF) localized in the pollen tube membrane (Meng et al, 2014a). This ABCF-mediated S-RNaseuptake pathway was also required for SI in Petunia species.…”
Section: Self-incompatibility Events That Arrest Self-pollen Tube Gromentioning
confidence: 99%